2014
DOI: 10.1063/1.4876129
|View full text |Cite
|
Sign up to set email alerts
|

Large scale two-dimensional arrays of magnesium diboride superconducting quantum interference devices

Abstract: Magnetic field sensors based on two-dimensional arrays of superconducting quantum interference devices were constructed from magnesium diboride thin films. Each array contained over 30 000 Josephson junctions fabricated by ion damage of 30 nm weak links through an implant mask defined by nano-lithography. Current-biased devices exhibited very large voltage modulation as a function of magnetic field, with amplitudes as high as 8 mV.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
8
0
1

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
0
8
0
1
Order By: Relevance
“…Large arrays have been produced [4,31,32] with up to 36 000 JJ. We recently showed that a 4000 JJ SQIF can have a transfer factor ∂V DC /∂B ∼ 1000 V /T [33,34] which is very encouraging.…”
Section: Introductionmentioning
confidence: 99%
“…Large arrays have been produced [4,31,32] with up to 36 000 JJ. We recently showed that a 4000 JJ SQIF can have a transfer factor ∂V DC /∂B ∼ 1000 V /T [33,34] which is very encouraging.…”
Section: Introductionmentioning
confidence: 99%
“…However, with a transition temperature of 9.25 K, practical operating temperatures for Nb devices are around 4 K and require expensive cryogenic cooling with large power requirements. The simple and cheapto-fabricate compound MgB 2 , with a high critical temperature of 40 K, large superconducting energy gaps greater than 2 meV, and small penetration depth of ∼40 nm, offers a promising alternative [3]- [6] in higher operating speed and temperatures than Nb circuits.…”
Section: Introductionmentioning
confidence: 99%
“…Similar electronic structures between S and N layers and a finite SC pairing interaction in the N layer are considered as sources for the enhanced proximity effect 13,14,16,24 . Conventional superconductor MgB 2 with relatively high T c of 40 K is a good candidate for GPE realization via the ion irradiation technique because of its large superconducting coherence length, metallicity, and large superconducting energy gap 25,26 .…”
Section: Introductionmentioning
confidence: 99%